Copper chloride as an extractant for estimating the potentially reactive aluminum pool in acid soils - Juo, A.S.R.; Kamprath, E.J. (Wiley, 1979)
The reactive Al pool in selected Ultisols, Oxisols, and Histosols from Africa, South America, and North Carolina was estimated by extraction with 1N CuCl2. The Al-saturated clay minerals with and without interlayered hydroxy-Al were used to compare the extractability of Al by 1N CuCl2 and 1N KCl. The 1N solutions of KCl and CuCl2 were equally effective in extracting exchangeable Al from an Al saturated montmorillonite. The 1N CuCl2 solution, however, extracted almost twice as much Al from an Al saturated vermiculite containing a hydroxy Al interlayer as compared with 1N KCl. Generally, more than twice as much Al was extracted from acid surface soils (< pH 5) by 1N CuCl2 than by 1N KCl suggesting that Al bound by organic matter was being extracted by the CuCl2.